2015
DOI: 10.1039/c5nr06035d
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of ultrathin AuPd alloy shells of irregularly shaped Au@AuPd nanoparticles with high-index facets on enhanced performance of ethanol oxidation

Abstract: In this study, irregularly shaped, concave cuboidal Au@AuPd nanoparticles (ISCC-Au@AuPd NPs) with high-index facets were synthesized via Pd overgrowth on pre-formed ISCC-Au NPs with a concentration of Pd precursors as low as 2%. The AuPd alloy nature of the resulting shells was confirmed by X-ray photoelectron spectroscopy, cyclic voltammogram analysis, and energy dispersive X-ray spectroscopy. Among the irregularly shaped NPs obtained, the ISCC-Au97.5@Au0.5Pd2.0 NPs display the largest electrochemically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…Fig. 3d compares the specific and mass activities of Pd2Sn:P/C with reported Pd-based catalysts showing that the simultaneous incorporation of Sn and P effectively improved the Pd activity toward EOR [9,12,16,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Additionally, the potential increase required to rise the current density was also significantly low for Pd2Sn:P/C, especially when compared with commercial Pd/C, as noted in the Tafel plots displayed in Fig.…”
Section: Pd2sn:p Nanorodsmentioning
confidence: 68%
“…Fig. 3d compares the specific and mass activities of Pd2Sn:P/C with reported Pd-based catalysts showing that the simultaneous incorporation of Sn and P effectively improved the Pd activity toward EOR [9,12,16,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Additionally, the potential increase required to rise the current density was also significantly low for Pd2Sn:P/C, especially when compared with commercial Pd/C, as noted in the Tafel plots displayed in Fig.…”
Section: Pd2sn:p Nanorodsmentioning
confidence: 68%
“…The morphology of the catalyst was determined by high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM). The particle size histogram was used to determine the exact particle size of metal nanoparticles on the surface of the synthesized catalyst [29] as shown in Figure 2. The particles appear to be deposited on rGO with an average mean size of 8.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…8,11,39 In a reported TEM study on nanoporous Au, an out-of-plane tensile strain is observed by nanobeam electron diffraction (NBD). 8 The authors attributed the excellent MOR performance of their nanoporous Au to the tensile strain.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 The electrocatalytic activity of Au depends on many factors such as size, 1,7 surface facet, 8 and defect 9,10 involving steps, kinks, stacking faults, twin boundaries, dislocations, etc. 11,12 These defects are considered as catalytically active sites due to their high surface energy, which promotes ionization and adsorption of intermediate reactants, such as OH À in electrolytes. 13,14 Therefore, precise control over the shape, size, and defect of Au nanostructures is the key to achieving excellent electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%